Chapter 4 Workshop-Didaktik for Cooperation in a Contingent World - Werler, Tobias (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"Based on the idea that contingency frames people's view of the world, the text examines how cooperation is still possible. It is argued that cooperation is a human constant (Tomsello), as well as a skill and craft to be unfolded again (Sennett). In order to facilitate teaching and learning processes focussing on the emergence of cooperation, a "Workshop Didactic" is developed. Such a didactic is particularly powerful in enabling people to deal with the challenges of unforeseen situations."